1993
DOI: 10.1063/1.464292
|View full text |Cite
|
Sign up to set email alerts
|

Reaction dynamics of C(1D)+H2(v)→CH(X 2Π)+H

Abstract: The CH(X 2Π,v,J,Ω,Λ) product state distribution from the reaction C(1D)+H2(v)→CH+H was determined by laser-induced fluorescence (LIF) where the B 2Σ–X 2Π transitions were probed. Most of the available energy is released as translation. A nearly thermal rotational distribution is obtained for CH(v=0,1). Only a small fraction, 4.1×10−4, of the CH products is formed in the vibrationally excited state. A higher propensity for the production of CH in the symmetric Π(A′) Λ sublevels is evident. For studying the infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…It can be seen that, most CH products are populated on the ground vibrational state, and only a few are populated on the ν ′ = 1 state, which is consistent with the experimental measurements. 14,15 The ICS (ν ′ = 1) has a visible contribution only at E c > 0.1 eV and then increases monotonically with the collision energy, whereas the ICS (ν ′ = 0) shows an opposite behavior. The product vibrational branching ratio defined as the ratio between the ICS (ν ′ = 1) and the ICS (ν ′ = 0) is 0.087 at the collision energy of 0.166 eV, which is consistent with the experimental value of 0.04.…”
Section: Product State Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be seen that, most CH products are populated on the ground vibrational state, and only a few are populated on the ν ′ = 1 state, which is consistent with the experimental measurements. 14,15 The ICS (ν ′ = 1) has a visible contribution only at E c > 0.1 eV and then increases monotonically with the collision energy, whereas the ICS (ν ′ = 0) shows an opposite behavior. The product vibrational branching ratio defined as the ratio between the ICS (ν ′ = 1) and the ICS (ν ′ = 0) is 0.087 at the collision energy of 0.166 eV, which is consistent with the experimental value of 0.04.…”
Section: Product State Distributionsmentioning
confidence: 99%
“…Experimentally, a number of kinetic and dynamical studies on the title reaction and its isotopic variants have been reported, [10][11][12][13][14][15][16][17][18][19] including several crossed molecular-beam (CMB) experiments. [16][17][18][19] In particular, Casavecchia and coworkers 16,18 measured the product angular and velocity distributions for the C( 1 D) + H 2 reaction at the collision energies of 7.8 and 16.0 kJ mol −1 , and the thermal rate coefficients for the C( 1 D) + H 2 reaction and its isotopic variants have been measured by Sato et al 15 On the theoretical side, Bussery-Honvault et al have developed a global ab initio potential energy surface (BHL PES) for the singlet ground state (1 1 A ′ ).…”
Section: Introductionmentioning
confidence: 99%
“…1,2 There have been experimental investigations of the C͑ 1 D͒ +H 2 reaction concerning the product internal energy distribution [3][4][5][6] and the kinetics. [6][7][8][9] In particular, the most recent experimental value 9 of the rate constant at 300 K is ͑2.0Ϯ 0.6͒ ϫ 10 −10 cm 3 s −1 .…”
Section: Introductionmentioning
confidence: 99%
“…Again, energy deposited in the v ¼ 1 vibrational level of H 2 may enhance the probabilities for the reaction pathways which are otherwise negligible in the H 2 (v ¼ 0) reactions [52]. Like this case, the vibrational excitation of H 2 helps open up new reaction pathways in the reactions with C( 1 D) and O( 3 P) [53,54] or increased rotational excitation of HD (v ¼ 1) in the reaction with D [25,55]. An active focus to find how energy is deposited and released was carried out in the Mg(3p 1 P) þ H 2 (v ¼ 1) reaction [24].…”
Section: Gas Cell Studies By the Pump-probe Techniquementioning
confidence: 92%
“…An active focus to find how energy is deposited and released was carried out in the Mg(3p 1 P) þ H 2 (v ¼ 1) reaction [24]. Hydrogen molecules in v ¼ 1, j ¼ 0-3 are prepared by using stimulated Raman pumping (SRP) [22][23][24][25][52][53][54][55].…”
Section: Gas Cell Studies By the Pump-probe Techniquementioning
confidence: 99%